Cats on the Couch: The Experimental Production of Animal Neurosis. Issue 1 (23rd February 2016) - Winter, Alison
Argument: In the 1940s–50s, one of the most central questions in psychological research related to the nature of neurosis. In the final years of the Second World War and the following decade, neurosis became one of the most prominent psychiatric disorders, afflicting a high proportion of military casualties and veterans. The condition became central to the concerns of several psychological fields, from psychoanalysis to Pavlovian psychology. This paper reconstructs the efforts of Chicago psychiatrist Jules Masserman to study neurosis in the laboratory during the 1940s and 1950s. Masserman used Pavlovian techniques in a bid to subject this central psychoanalytic subject to disciplined scientific experimentation. More generally, his project was an effort to bolster the legitimacy of psychoanalysis as a human science by articulating a convergence of psychoanalytic categories across multiple species. Masserman sought to orchestrate a convergence of psychological knowledge between fields that were often taken to be irreconcilable. A central focus of this paper is the role of moving images in this project, not only as a means of recording experimental data but also as a rhetorical device. The paper argues that for Masserman film played an important role in enabling scientific observers (and then subsequent viewers) to see agency and emotion in the animals they observed.